1989
DOI: 10.1017/s0043174500072076
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Soybeans (Glycine max) with Reduced Rates of Postemergence Herbicides

Abstract: Field studies were conducted at three sites in Missouri in 1986 and 1987 to evaluate the performance of below-label rates of bentazon, acifluorfen, and chlorimuron tank mixed with sethoxydim and applied to soybeans 7 and 14 days after planting to evaluate broadleaf and grass weed control and weed seed production. Sequential applications of 0.25X-labeled rates of all three broadleaf herbicides tank mixed with 0.5X sethoxydim rates controlled giant foxtail, velvetleaf, and common cocklebur equivalent to one appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
3
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 15 publications
4
104
3
2
Order By: Relevance
“…In field experiments, dicamba, triclopyr, and other herbicides required greater use rates to control the R biotype when plants were ,10 cm tall with multiple (.4) branches, compared with seedlings treated before branching (McCullough, personal observation). Reduced control from herbicides applied to mature weeds has been reported for common cocklebur (Xanthium strumarium L.), pitted morningglory (Ipomoea lacunosa L.), smooth pigweed (Amaranthus hybridus L.), and other annual weeds (Barrentine 1989;DeFelice et al 1989;Klingman et al 1992). Furthermore, mature weeds may have produced viable seed that could further spread resistant populations after control.…”
Section: Resultsmentioning
confidence: 99%
“…In field experiments, dicamba, triclopyr, and other herbicides required greater use rates to control the R biotype when plants were ,10 cm tall with multiple (.4) branches, compared with seedlings treated before branching (McCullough, personal observation). Reduced control from herbicides applied to mature weeds has been reported for common cocklebur (Xanthium strumarium L.), pitted morningglory (Ipomoea lacunosa L.), smooth pigweed (Amaranthus hybridus L.), and other annual weeds (Barrentine 1989;DeFelice et al 1989;Klingman et al 1992). Furthermore, mature weeds may have produced viable seed that could further spread resistant populations after control.…”
Section: Resultsmentioning
confidence: 99%
“…In this study four chemical herbicides, chlorimuron, imazaquin, imazethapyr and MSMA, were chosen that are widely used to control common cocklebur in various geographical areas 27–30, 32, 33. They were used as commercial formulations: chlorimuron 250 g kg −1 DG (CLASSIC ® , DuPont), imazaquin 700 g kg −1 DG (Scepter ® , American Cyanamid), imazethapyr 700 g kg −1 DG (Pursuit ® , American Cyanamid) and MSMA 510 g liter −1 SL (Luxembourg & ISK Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…However, the efficacy of conventional herbicides and A helianthi has not been previously evaluated on MSC. Therefore, in the present study, we compared the response of MSC with that of normal common cocklebur (NCC) varieties to the mycoherbicide agent A helianthi 25 and to several conventional herbicides which are known to control the latter27–30 in various geographical areas.…”
Section: Introductionmentioning
confidence: 99%
“…Herbicide interactions have been extensively investigated and reported with respect to synergism, antagonism, and additivity (Colby 1967;Hatzios and Penner 1985). Previous research has demonstrated the benefit of utilizing reduced rates of selected soybean herbicides in mixtures to enhance weed control and diminish the development of resistant weed biotypes (Defelice et al 1989;Gressel 1990;Starke and Oliver 1998). However, little information has been published examining reduced rates of corn herbicides in mixtures for common lambsquarters control.…”
Section: Introductionmentioning
confidence: 99%